2017
DOI: 10.1093/nar/gkx1093
|View full text |Cite
|
Sign up to set email alerts
|

AutDB: a platform to decode the genetic architecture of autism

Abstract: AutDB is a deeply annotated resource for exploring the impact of genetic variations associated with autism spectrum disorders (ASD). First released in 2007, AutDB has evolved into a multi-modular resource of diverse types of genetic and functional evidence related to ASD. Current modules include: Human Gene, which annotates all ASD-linked genes and their variants; Animal Model, which catalogs behavioral, anatomical and physiological data from rodent models of ASD; Protein Interaction (PIN), which builds intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 19 publications
1
41
0
Order By: Relevance
“…Autism spectrum disorders (ASD), characterized by abnormal social interaction and communication and restricted interests and repetitive behaviors, are a group of complex neurodevelopmental disorders (Christensen et al, 2016;de la Torre-Ubieta et al, 2016). To date, >800 ASD-related genes have been included in the database AutDB (Pereanu et al, 2018), suggesting the extreme genetic heterogeneity of this disease (Bi et al, 2012;Jeste and Geschwind, 2014;Li et al, , 2017. However, the molecular etiologies of these genes in ASD have been demonstrated only in limited animal models Deriziotis et al, 2014;Huang et al, 2014;Katayama et al, 2016;Liu et al, 2016;Orosco et al, 2014;Peç a et al, 2011;Peñ agarikano et al, 2011;Schoch et al, 2017;Wang et al, 2016), leaving the challenge of translating autism genetics to clinical applications (Vorstman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Autism spectrum disorders (ASD), characterized by abnormal social interaction and communication and restricted interests and repetitive behaviors, are a group of complex neurodevelopmental disorders (Christensen et al, 2016;de la Torre-Ubieta et al, 2016). To date, >800 ASD-related genes have been included in the database AutDB (Pereanu et al, 2018), suggesting the extreme genetic heterogeneity of this disease (Bi et al, 2012;Jeste and Geschwind, 2014;Li et al, , 2017. However, the molecular etiologies of these genes in ASD have been demonstrated only in limited animal models Deriziotis et al, 2014;Huang et al, 2014;Katayama et al, 2016;Liu et al, 2016;Orosco et al, 2014;Peç a et al, 2011;Peñ agarikano et al, 2011;Schoch et al, 2017;Wang et al, 2016), leaving the challenge of translating autism genetics to clinical applications (Vorstman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The preferential effect on large mRNAs is likely mediated by direct FMR1 binding, because the average size of target proteins common to both this study and (7) was 1841 amino acids. Furthermore, genes linked to autism as a group are significantly longer than average (16,20).…”
mentioning
confidence: 99%
“…In order to determine whether characteristics of transcripts encoded by ASD/ID genes distinguish them from other neuronally-expressed genes, we examined general properties of all transcripts expressed in the juvenile mouse cortex (Das Sharma et al 2019). We classified SFARI Class I and Class II (Abrahams et al 2013;Pereanu et al 2017) autism genes as "ASD genes" and found that they differ from other neuronally-expressed genes in several ways. (1) ASD/ID genes as a group encode proteins much larger than average.…”
Section: Asd/id Genes Tend To Encode Large Proteinsmentioning
confidence: 99%